Integrasi Platform Instagram & Website Untuk Meningkatkan Penjualan Pada UMKM XYZ - Fajar Reskiyani; Muhammad Jamil; Muhammad Ashdaq (Pusat Penelitian dan Pengabdian bagi Masyarakat Politeknik Negeri Tanah Laut, 2026)
This study focuses on the importance of utilizing digital marketing strategies to increase sales for micro, small, and medium enterprises (UMKM) in the digital era, particularly through the integration of Instagram and website platforms. The purpose of this study is to examine the effect of integrating these digital platforms on increasing the sales of UMKM XYZ. The research method used is Research & Development-based with a Four-D model, which includes needs analysis, design, and testing of the implementation of digital strategies. The main results show a significant increase in the number of products sold and revenue, from 178 products and IDR 12,555,000 to 275 products and IDR 17,620,000 after platform integration, with an increase in the number of followers and consumer interactions. The implication of this research is that the application of digital technology and engaging content can expand market reach and increase customer trust, thereby supporting the growth of UMKM. In conclusion, digital platform integration is an effective strategy that UMKM can use to increase sales and competitiveness in an increasingly competitive market.